2017
DOI: 10.1007/s12015-016-9715-z
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Content of Extracellular Vesicles Derived from Expanded Human Umbilical Cord Blood-Derived CD133+ and Human Bone Marrow-Derived Mesenchymal Stem Cells Partially Explains Why both Sources are Advantageous for Regenerative Medicine

Abstract: Adult stem cells have beneficial effects when exposed to damaged tissue due, at least in part, to their paracrine activity, which includes soluble factors and extracellular vesicles (EVs). Given the multiplicity of signals carried by these vesicles through the horizontal transfer of functional molecules, human mesenchymal stem cell (hMSCs) and CD133 cell-derived EVs have been tested in various disease models and shown to recover damaged tissues. In this study, we profiled the protein content of EVs derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Therefore, we hypothesized that huc-MSC-EVs are rich in antioxidant proteins. Lots of antioxidant enzymes that regulated the redox status had been found enriched in MSC-EVs, including catalase, SOD1, SOD2, glutathione peroxidase, and others (49). Moreover, Yan et al (32) demonstrated that the specific antioxidant enzyme glutathione peroxidase 1 in huc-MSC exosomes was required for the recovery of hepatic oxidant injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that huc-MSC-EVs are rich in antioxidant proteins. Lots of antioxidant enzymes that regulated the redox status had been found enriched in MSC-EVs, including catalase, SOD1, SOD2, glutathione peroxidase, and others (49). Moreover, Yan et al (32) demonstrated that the specific antioxidant enzyme glutathione peroxidase 1 in huc-MSC exosomes was required for the recovery of hepatic oxidant injury.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the underlying mechanisms, we analyzed the publicly available database. Interestingly, Angulski et al (49) showed that MnSOD, which is mainly located in mitochondrial components, was found in bone marrow (BM)-MSC-EVs using liquid chromatographytandem mass spectrometry analysis, suggesting that MnSOD might have a specific function (Fig. 6A).…”
Section: Mnsod In Huc-msc-evs Prevents Hepatocytes From Oxidative Strmentioning
confidence: 99%
“…Recently, special attention has been paid to stem cell-derived microvesicles (MVs), which transport a wide range of cargo including proteins, organelles, RNA, miRNA and bioactive lipids [ 24 , 25 ]. MVs are enriched in bioactive molecules, thus they play a pivotal role in many biological processes, including tissue regeneration.…”
Section: Mf In Stem Cell Signaling and Differentiationmentioning
confidence: 99%
“…for better understanding of the functions in each vesicle type and delineating the appropriate use of each EV in therapeutic procedures 59 . For protein content, expanded CD133ĂŸ-EVs might be better inducers or modulators of angiogenesis (e.g.…”
Section: >20 Generationsmentioning
confidence: 99%